Report on 2025 additions to the KMD application and web dashboard - Sidjesse, Makokha; Dhulipala, Ram; Singh, Kanika (International Livestock Research Institute, 2025)
Under the AICCRA project, the Kenya Cluster has strengthened climate resilience for smallholder farmers by enhancing the capabilities of the Kenya Meteorological Department (KMD). A central achievement of this collaboration is the co-development and 2025 refinement of the AICCRA-KMD mobile application. This Android-based tool is designed to revolutionize field data collection and the delivery of climate-informed agro-advisories. It enables a network of County Directors, extension staff, and enumerator farmers across eight arid and semi-arid counties to manually record and upload daily rainfall and critical weekly crop data, including pest incidence and yield information. The application ensures real-time data integration with a web dashboard, minimizing collection errors and streamlining analysis. By providing a reliable channel for ground-truthed, weather-linked data, the AICCRA-KMD app empowers stakeholders with actionable insights, facilitating data-driven decision-making and supporting the broader scaling of climate-smart agriculture practices in Kenya.